Implementation Environment Learning virtual (LPV) in Training Indonesian for speaker foreign Level Beginner - Jamaluddin Jamaluddin; Nursidah Nursidah; Andi Rachmawati Syarif; Sam Hermansyah; Basuki Rahmat MS (La Ogi : English Language Journal, 2023)
This aim For describe application Environment Learning virtual ( Virtual Learning Environment ) in the BIPA training for the Beginner Level that was held by Muhammadiyah Sidenreng Rappang University. Implementation of Virtual Learning Environment (LPV) is carried out using four platforms as learning media online and remotely during the Covid-19 pandemic. The four platforms are zoom media as a form of synchronous learning, as well as asynchronous learning through use of LMS created and managed by Muhammdiyah Sidenreng Rappang University , Telegram social media and electronic mail or e-mail. This article uses qualitative method, namely describing the activities of the online BIPA learning process and long distance. The data includes learning activities that are processed based on activity categories learners and platforms used in learning which are then analyzed. Based on the findings, integration of LPV in Beginner Level BIPA learning with student cross country give bid Which promising for process learning online and remotely. LPV provides interactive learning tools as well communicative so that the learning process can be accepted by students wherever they are is at. Therefore, LPV integration for BIPA learning can be a reliable choice in online and cross-border learning. However, the refinement of LPV integration for BIPA, especially the Beginner Level, must continue to be developed in the future so that the goals goal Language Indonesia as Language international Can quick materialized.